Resentimiento en adolescentes escolares de condición socio-económica alta y baja - León, Ramón (1988)
Resentment was assessed via two measures in low-SES male and female high school adolescent students and high-SES female students. Chi-square demostrated no item-especific sex -differences in the low-SES students with León el al. Scale. But low-SES females had significant higher levels of resentment than their high-SES counterparts, with item-specific differences too. With the Buss-Durkee resentment sub-scale, sex -differences between SES students were found only in one of the eigth items (item 7, ooncerning bad luck in life), but lowS ES females differed significantly front high-SES females in four items out of eigth items.